Some Regularities of Persistent Forms of Clinical Isolates of Gram-Negative Bacteria Formation - N. N. Markelova; A. V. Tutelyan; V. M. Pisarev; A. M. Gaponov (Антибиотики и Химиотерапия, 2020)
The ability of clinical isolates Escherichia coli (16), Klebsiella pneumoniae (20), Pseudomonas aeruginosa (12) to survive under the influence of high bactericidal concentrations of meropenem was studied. After 2 and 4 hours of exposure to the antibiotic, the authors have identified antibiotic-tolerant populations of bacteria (persisters) represented by ordinary sized colonies and SCV type (small variant colony). The number of colonies that have grown after the antibiotic attack of each isolate of above-mentioned species of bacteria positively correlated (P0.05). Thus, it has been shown that kinetic parameters of bacterial growth in a medium can designate their level of persisters formation in the same medium after the addition of an antibiotic.